Effect of Ta Content on Microstructure and Phase Transformation Temperatures of Ti75.5-Nb25.5 (%at.) Alloy - Mohammed, Safar Saeed; Dagdelen, Fethi; Qader, Ibrahim Nazem (Gazi Univ, 2022)
beta-titanium shape memory alloys are used as shape memory-based biomedical applications and superelastic materials because they are made up of non-toxic components. Also, their behaviors are more semilar with that of human bone and dental biological tissues, such as biocompatibility, superior corrosion resistance, low density, and low modulus of elasticity. In the current study, the effect of Ta additive on the physical properties of Ti-Nb alloy has been investigated. Ti-Nb-Ta alloy samples were produced such that the Tantalum (Ta) element was substituted instead of Niobium (Nb), and the induction arc melting was used to melting the mixed powders. To investigate the crystal structure, microstructure, and phase transformation temperatures of all samples, the X-Ray Diffraction (XRD), Scanning Electron Microscopic (SEM), and Diffraction Scanning Calorimetry (DSC) measurements have been used. Both beta rich and alpha peaks were observed in the XRD and SEM measurements. Also, the DSC results revealed that the Ti-Nb-Ta alloys have only austenite transformation temperatures and their phase austenite phase transformation were decreased by the effect of Ta additive, additionally, the enthalpy change in E3 sample ( Ti75.5 Nb22.5 Ta2 (%at)) has the highest value, while E4 sample ( Ti75.5 Nb21.5 Ta3 (%at)) has the lowest respective value.
Keywords: Shape memory alloy; ?-titanium alloy; Ti-Nb-Ta; microstructure